Analisis Faktor-faktor yang Mempengaruhi Penentuan Jenis Pemeliharaan Embung Irigasi - Bria, Melchior; Sutirto, Sutirto; Muda, Anastasia H (MEDIA KOMUNIKASI TEKNIK SIPIL, 2019)
Maintenance of good and sustainable irrigation ponds have an impact on ensuring the sustainability of the irrigation system. For this reason, it is necessary to develop a reservoir maintenance model based on multicriteria analysis relating to the type of maintenance. The method used Structural Equation Model (SEM) with the WarpPLS approach. The criteria used Structural Stability, Economy / Finance, and Physical & Environmental. The findings obtained variable structural stability has a very significant effect on the maintenance of irrigation ponds (r <0.01 and β = 0.73). Economic / financial variables have not significant effect on reservoir maintenance where r = 0.3 and β = 0.03. Physical and environmental variables also did not directly influence the maintenance of ponds with r = 0.29 and β = 0.03. However, the physical & environmental variables significantly influenced structural stability with r <0.01 and β = 0.32. Physical and environmental variables also significantly influenced economic/financial where r <0.01, and β = 0.45. This finding supported various previous studies for structural stability variable but different for economic/financial variables that did not significantly affect by the determination of reservoir types.